2018
DOI: 10.1096/fj.201700430r
|View full text |Cite
|
Sign up to set email alerts
|

Novel imaging of the prostate reveals spontaneous gland contraction and excretory duct quiescence together with different drug effects

Abstract: Prostate carcinoma and benign prostate hyperplasia (BPH) with associated lower urinary tract symptoms (LUTS) are among the most prevalent and clinically relevant diseases in men. BPH is characterized by an enlargement of prostate tissue associated with increased tone of smooth muscle cells (SMCs) which surround the single glands composing the prostate. Secretions of the glands leave the prostate through local excretory ducts during the emission phase of ejaculation. Pharmacological treatment of BPH suggests di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…TAD, sildenafil and vardenafil are employed to treat erectile dysfunction (ED) through the specific inhibition of cGMP-specific PDE5, responsible for cGMP degradation in the corpus cavernosum [43]. Currently, PDE5i are largely used as daily treatment for benign prostatic hyperplasia (BPH)-related lower urinary tract symptoms (LUTS) where they reduce spontaneous contractility of the glands, thereby reducing the muscle tone of the genitourinary tract [44] even if a specific inhibitory growth pattern on prostate tissue has not been clearly documented. Fibbi et al reported PDE5 immunolocalization mainly in the fibromuscular stroma and vascular (endothelial and stem cells) in the rat and human prostate from BPH subjects [45]; by contrast, Ückert et al immunolocalized PDE5 expression also at glandular and subglandular areas of human prostate cancer patients [46].…”
Section: Discussionmentioning
confidence: 99%
“…TAD, sildenafil and vardenafil are employed to treat erectile dysfunction (ED) through the specific inhibition of cGMP-specific PDE5, responsible for cGMP degradation in the corpus cavernosum [43]. Currently, PDE5i are largely used as daily treatment for benign prostatic hyperplasia (BPH)-related lower urinary tract symptoms (LUTS) where they reduce spontaneous contractility of the glands, thereby reducing the muscle tone of the genitourinary tract [44] even if a specific inhibitory growth pattern on prostate tissue has not been clearly documented. Fibbi et al reported PDE5 immunolocalization mainly in the fibromuscular stroma and vascular (endothelial and stem cells) in the rat and human prostate from BPH subjects [45]; by contrast, Ückert et al immunolocalized PDE5 expression also at glandular and subglandular areas of human prostate cancer patients [46].…”
Section: Discussionmentioning
confidence: 99%
“…Wahdera [14] postulated that acinar dilation may occur from chronic reflux of semen or urine secondary to pelvic muscle contraction. Nor was there evidence of ductal narrowing from scarring or chronic effects of prolonged contraction from drug effects [15].…”
Section: Discussionmentioning
confidence: 99%
“…PDE5i are largely used as daily treatment for BPH-related LUTS where they reduce spontaneous contractility of the glands, thereby reducing the muscle tone of the genitourinary tract [8]. The reported up-regulation of PDE5 in hyperplastic human prostate could provide a rationale for the high efficacy of PDE5i in treating patients with LUTS/BPH with/without ED [27].…”
Section: Pde5i and Prostatementioning
confidence: 99%
“…Initial studies in transgender males demonstrated that small PDE5 amounts are present in different extragenital tissues from humans, such as skeletal muscle, heart, lung, and adrenal gland [6]. Successive preclinical and clinical observations, coming from our and other research units, demonstrated that tadalafil modulates the aromatase (ARO) activity and the expression and function of the androgen receptor (AR) in lines of bone, breast, prostate, adipose and muscle cells, suggesting a possible direct interaction with steroid hormones [3,[7][8][9]. Thus, the aim of this review will be to summarize the putative effect of tadalafil on ARO activity and on steroid hormone receptor(s) expression by using both in vitro and in vivo different cellular models and to translate them into possible clinical applications.…”
Section: Introductionmentioning
confidence: 99%